The Inflammasome Signaling Proteins ASC and IL-18 as Biomarkers of Psoriasis - Forouzandeh, Mahtab; Besen, Jaren; Keane, Robert W.; de Rivero Vaccari, Juan Pablo (Frontiers in Pharmacology, 2020)
Inflammasome activation in the innate immune response plays a role in the pathogenesis of psoriasis largely due to the increased levels of pro-inflammatory cytokines. However, the precise role of inflammasomes in psoriasis (Ps) and psoriatic arthritis (PsA) is largely undefined. To establish the reliability of inflammasome signaling proteins as diagnostics and predictive biomarkers of clinical severity in this disease population, serum from healthy donors and patients with Ps/PsA were analyzed for the protein expression of caspase-1, apoptosis-associated speck-like protein containing a caspase-recruitment domain (ASC), interleukin (IL)-1β and IL-18 levels to determine cut-off points, positive and negative predictive values, and receiver operator characteristic (ROC) curves. Our data revealed that ASC and IL-18 proteins were significantly higher in the Ps group when compared to healthy controls. The area under the curve (AUC) for ASC was 0.9224 with a cut-off point of 321.8 pg/ml, while IL-18 had an AUC of 0.7818 and a cut-off point of 232.1 pg/ml. In addition, levels of IL-18 had a statistically significant linear correlation with that of ASC with an adjusted R squared of 0.2566, indicating that approximately 25% of IL-18 levels could be explained by ASC levels in serum. Our findings indicate that ASC and IL-18 play a significant role in the inflammatory response associated with the pathology of Ps. These inflammasome proteins appear to be key biomarkers in determining diagnoses in this patient population.